HUBUNGAN PERILAKU PICKY EATER DENGAN STATUS GIZI PADA ANAK USIA PRA SEKOLAH - Wahyuningsih, Sri; Anggraini, Marisa Lia; Rosa, Audrey Faiza (Ensiklopedia of Journal, 2024)
The prevalence of monitoring the nutritional status of children in the city of Padang in 2017 states that the District Pauh has the highest number of 300 undernourished people. Known nutritional status data by category BB / U is a toddler with undernourishment by 60 (20%). Malnutrition caused because eating one of which is the behavior of a picky eater. Picky eater occurs in pre-school age children experience changes in eating patterns generally picky eating. Behavior picky eater is a risk of the child may experience problems nutritional status. The purpose of this study was to determine the behavior of Picky Eater Relationship with Nutritional Status on Preschooler in kindergarten Al Hidayah Village Padang Pauh Subdistrict Cupak Tangah 2019.This type of research analytic survey with cross sectional study. The sampling technique is "Total Sampling" with a sample of 48 parents or caregivers who have pre-school children in kindergarten Al Hidayah. This study used the weighing instrument BB / U and questionnaires Child Eating Behaviour Questionnaire (CEBQ). Univariate analysis shown in the table of frequency distribution and bivariate using Chi-square test. The results showed less than half (25.0%) children had good nutritional status, more than half (52.1%) children had behavioral picky eater and there is a relationship between the behavior of a picky eater with nutritional status among preschool children in kindergarten Al Hidayah Village Padang Pauh Subdistrict Cupak Tangah 2019 p value = 0.001 (p <0.05). From the results of this study it can be concluded that nutritional status is related to picky eating behavior. Suggested for kindergarten to be more active Hidayah socialize programs nutritional status of children by providing counseling, especially parents about the behavior of a picky eater with nutritional status of pre- school children.